Governing for sustainable energy system change: Politics, contexts and contingency. (February 2016) - Kuzemko, Caroline; Lockwood, Matthew; Mitchell, Catherine; Hoggett, Richard
Abstract: This paper offers a new, interdisciplinary framework for the analysis of governing for sustainable energy system change by drawing together insights from, and offering critiques of, socio-technical transitions and new institutionalist concepts of change. Institutions of all kinds, including rules and norms within political and energy systems, tend to have path-dependent qualities that make them difficult to change, whereas we also know that profound change has occurred in the past. Current decisions to pursue climate change mitigation by dramatically changing how energy is produced and used depend to some extent on finding the right enabling conditions for such change. The approach adopted here reveals the highly political and contingent nature of attempts to govern for innovations, how political institutions mediate differently between forces for sustainable change and forces for continuity, as well as specific interactions between governance and practice change within energy systems. It concludes that it is only by being specific about the contingent nature of governing for innovations, and about how this affects practices in energy systems differently, that those of us interested in sustainability can credibly advise policy makers and drive for greater change.